2016
DOI: 10.1111/1468-4446.12200
|View full text |Cite
|
Sign up to set email alerts
|

The cosmopolitan contradictions of planetary urbanization

Abstract: This paper explores the empirical, conceptual and theoretical gains that can be made using cosmopolitan social theory to think through the urban transformations that scholars have in recent years termed planetary urbanization. Recognizing the global spread of urbanization makes the need for a cosmopolitan urban sociology more pressing than ever. Here, it is suggested that critical urban sociology can be invigorated by focusing upon the disconnect that Henri Lefebvre posits between the planetarization of the ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…For the community theory, Milligan (2012) and Wilson (2017) found that an income or wealth gap in the location where an individual lives adversely affected religious tolerance. Millington (2016) and Finke and Stark (2003) showed that individuals who live in cities (urban settings) tended to be more tolerant, simply because they lived in a culturally, ethnically, or racially diverse environment, relative to those who live in rural areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the community theory, Milligan (2012) and Wilson (2017) found that an income or wealth gap in the location where an individual lives adversely affected religious tolerance. Millington (2016) and Finke and Stark (2003) showed that individuals who live in cities (urban settings) tended to be more tolerant, simply because they lived in a culturally, ethnically, or racially diverse environment, relative to those who live in rural areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…And yet, amid the focus on the movement of ideas and policies across space in an era characterised by seemingly untrammelled globalisation, there are also repeated concerns in parts of Anglophone world that the West is not the only point of reference for planners, and that educators and students should listen more to the voices from the beyond the global North (for example, Carolini, 2018). And while there are vibrant international networks that "showcase the diverse tactics" of different international groups, which are sometimes "disregarded by professional [planning] practice" (Carolini, 2018, 4), planners in parts of the global North are being encouraged to embrace a widened "vocabulary of Southern urban practice" (Bhan, 2019, 15), especially when cities and regions are being increasingly interwoven, as they simultaneously "fold-in" and stretch-out across time and space (Simone, 2010;Millington, 2016). Internationalisation in this sense, may be interpreted as forming part of a broader project of public engagement against threats of populism, nationalism and intolerance (Amin, 2019, 7; see also Altbach and de Wit, 2018).…”
Section: Traces Beyond the Global Southmentioning
confidence: 99%
“…try to see things in a new way. In doing so it thinks about the how the urban sensorium is being changed in coincidence with changes in processes of urbanization; how such changes in sense are deployed strategically in order to facilitate more adaptive responses to these processes, thus building on work focused on the more cultural dimensions of urbanization’s impact on human life (Merrifield, 2013; Millington, 2016; Pow, 2017). While the inhabitants of urban spaces have always been multiple in terms of composition and outlook, this contribution attempts to rework the very grounds where inhabitation takes place, to imagine new territories of inhabitation within the confines of more familiar designations, such as urban core and urban periphery.…”
Section: Extending the Extendedmentioning
confidence: 99%